2007
DOI: 10.1002/jemt.20450
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Fatty Acids with Selective Chain Length by Imaging Time‐of‐Flight Secondary Ion Mass Spectrometry

Abstract: Localization of fatty acids in biological tissues was made by using TOF-SIMS (time-of-flight secondary ion mass spectrometry). Two cell-types with a specific fatty acid distribution are shown. In rat cerebellum, different distribution patterns of stearic acid (C18:0), palmitic acid (C16:0), and oleic acid (C18:1) were found. Stearic acid signals were observed accumulated in Purkinje cells with high intensities inside the cell, but not in the nucleus region. The signals colocalized with high intensity signals o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 57 publications
2
24
0
1
Order By: Relevance
“…Our results seem to be in agreement with a recent report based on TOF-SIMS imaging of rat duodenum ( 46 ). In this seminal study, strong signals corresponding to C16:0 and to the PI polar head ( m/z With respect to vE changes, a defi cit in serum vE in CF patients, attributed to intestinal malabsorption, is widely accepted ( 65,66 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results seem to be in agreement with a recent report based on TOF-SIMS imaging of rat duodenum ( 46 ). In this seminal study, strong signals corresponding to C16:0 and to the PI polar head ( m/z With respect to vE changes, a defi cit in serum vE in CF patients, attributed to intestinal malabsorption, is widely accepted ( 65,66 ).…”
Section: Discussionsupporting
confidence: 93%
“…PC1-4, principal component 1-4. 241) were found in the Lieberkühn crypt region; whereas the C18:2 signal was weak in the crypt and strong in the villus, C18:1 was predominant in villi, and C18:0 was ubiquitous ( 46 ). In our study, C18:2, an essential fatty acid, was mainly found in the epithelial border ( Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Most successful in terms of publications are the following three subjects: (1) investigations on the miscibility of lipids and proteins in Langmuir-Blodgett films in cooperation with two biophysics groups [28][29][30][31]. (2) Tissue slide analysis is performed by and/or in close co-operation with the group of Hakan Nygrenas will be shown by him in this session [32][33][34]. (3) In close cooperation with biochemistry groups of the University of Muenster we study animal cells from in vitro culture by ToF-SIMS analysis [26,35].…”
Section: Introductionmentioning
confidence: 99%
“…For positive ion spectra, Fig. 1(a) + (m/z 184, phosphocholine) [7,11] are associated with the control and MSCtreated MI tissues, not with the MI tissue, as the positive scores correspond to the positive loadings and vice versa ( Fig. 1(b)).…”
Section: Resultsmentioning
confidence: 93%